The Effectiveness Of Students Vocabulary Achievement Through Intensive Reading In MTs Al Washliyah Kolam - Nur Hasanah Batubara, Dahlia Sirait (Pusdikra Publishing, 2022)
This research aimed to obtain the empirical evidence of the effectiveness of Intensive reading on students’ reading comprehension. The sample of this research was students of class VII – I (as experimental groups) and VII – II (as control group) of the Mts Al Washliyah Kolam. The researcher used the Experimental Design as the method for the research. The students consists 2 groups, namely experimental group and control group. This research used pre-test and post-test.The result of the conclusion of t-test is that t-observed value : 11.38 with degree of freedom (df) = 76 is higher than the value of t-table (1,99). In conclusion, those findings in imply that the alternative (Ha) : Intensive Reading on vocabulary achievement is accepted and null hypothesis (Ho) is rejected. As a result, the impact of Intensive Reading has a significant effect on student vocabulary achievement.